How do students of different self-efficacy regulate learning in collaborative design activities? An epistemic network analysis approach - Chen, Peng; Yang, Dong; Lavonen, Jari; Metwally, Ahmed Hosny Saleh; Tang, Xin (Frontiers in Psychology, 2024)
Students' self-regulation skills and self-efficacy are linked to performance and are considered essential for lifelong learning. In this study, 60 students attending a university-level collaborative design course were recruited as participants. They were initially classified into three groups (high, mixed, and low self-efficacy (SE)) based on the initial test results. Then, students' written reflections were analyzed using epistemic network analysis (ENA), aiming to explore the characteristics and developmental trajectories of self-regulated learning (SRL). The results indicated that, compared with the other two groups, the high self-efficacy (HSE) group demonstrated (1) more behavioral characteristics of SRL in the performance and self-reflection stages, (2) an earlier development of interest in the task and recognition of its value during collaborative design activities, followed by the utilization of more cognitive and metacognitive strategies; and (3) an "anticipation-behaviorreflection" loop in the self-regulation process. Strategies for improving learners' SRL and future research directions were provided accordingly.